Zakon i obyčai v stepi kazachi srednego žuza i rossijskij kolonializm v XIX veke - Martin, Virginia (Istorija Kazachstana v zapadnych istočnikach, 2009)
"This study offers a reconstruction of the social, cultural and legal history of the Middle Horde Kazakh steppe within the Russian Empire in the nineteenth century. Using largely untapped archival records from Kazakhstan and Russia, as well as ethnographic research, administrative reports, the provincial press and scholarly analyses, it explores the cross-cultural encounter of laws, customs and judicial practices in the process of Russian empire-building at the local level."